Hydration and properties of ternary cement with calcareous filler and slag - Irassar, E. F.; Bonavetti, V. L.; Menéndez, G.; Carrasco, M. F. (Revista ALCONPAT, 2015)
Limestone filler (F) produces an increase of early hydration due to the physical effect (filling and heterogeneous nucleation). The dilution effect reduces this benefit limiting the F content. Granulated blast furnace slag reacts slowly causing the grain and pore size refinements, and improve mechanical and durable properties. In this paper, the hydration of cements with F (0-20%) and GBFS (0-35%) is studied using the model of Powers extended by Chen & Browers for slag. From the results of the hydration, the mechanical strength of concrete (w/cm = 0.50), and the pore segmentation process is analyzed in relation to the sorptivity rate. Results show that filler content should be limited for an adequate mechanical strength and long term durable properties and slag content should be limited for appropriate early properties Keywords: calcareous filler; slag; resistance; capillary absorption; hydration.